PERTIMBANGAN HAKIM DALAM MENENTUKAN HAK ASUH ANAK AKIBAT PERCERAIAN AGAMA HINDU DI BALI - Ni Putu Yuliana Kemalasari (Magister Hukum Pascasarjana Univeristas Ngurah Rai, 2019)
The prominent legal issues in balinese law can be classified in two problems, inheritance and purusa ( descendant ), purusa is an inherent status (comonly for male) after marriage. If there is later a divorce, the judge must consider the decision in applying the law that was enforced in deciding the divorce case. Referring to Balinese customary law, when there is a divorce, the child's custody will fall on the purusa / father because the child will become a descendant of the father's family, whereas in the Decision of the Supreme Court of the Republic of Indonesia number: 126K / Pdt. / 2001 dated August 28, 2003 states that